Working-class minority students' routes to higher education - Espinoza, Roberta. (Routledge research in education ;, 2012)
"While stories of working-class and minority students overcoming obstacles to attend and graduate from college tend to emphasize the individualistic and meritocratic aspect, this book - based in extensive empirical study of American high school classrooms, and in theories of social and cultural capital - examines the social relations that often underpin such successes, highlighting the significant formal and informal academic interventions by educators and other education professionals"--